Political Interests Versus the Supremacy of Law: A Critical Review of Constitutional Law Regarding the Abolition of Tom Lembong and Amnesty for Hasto Kristiyanto - Fakhry Amin; Souad Ahmed Ezzerouali (PATTIMURA Legal Journal, 2025)
Introduction: The President's authority to grant amnesty and abolition is a constitutional prerogative that provides flexibility in resolving legal issues with political and social implications, such as reconciliation and conflict resolution. Purposes of the Research: This research aims to provide a critical analysis regarding the granting of amnesty to Hasto Kristiyanto and the abolition granted to Tom Lembong from the perspective of constitutional law. Methods of the Research: This research is a normative legal study with a conceptual and legislative approach. Results Main Findings of the Research: The constitutional authority of the President to grant amnesty and abolition is a prerogative right that provides flexibility and special power to resolve legal issues related to political and social dimensions, such as reconciliation and conflict resolution. The case of granting amnesty to Hasto Kristiyanto and abolition to Tom Lembong has sparked a debate about the balance between the supremacy of law and political interests, where the decision has the potential to mature the subordination of law to political interests, thus demanding transparency and accountability so that the President's prerogative is not misused for short-term political gain. Therefore, a checks and balances mechanism involving the House of Representatives and high transparency must be implemented so that the President's authority can be exercised in an accountable manner and in favor of the people's interests as a whole.